Boo the Library Ghost - Paige, Becky (San Diego, CA : Silver Dolphin Books, 2024)
"The library is Poppys favorite place to go but its haunted by a ghost named Boo who loves to frighten visitors away. Boo casts eerie shadows, rips out pages, and knocks books off the shelves. However, brave Poppy refuses to leave-she just wants to read in peace! Poppy soon realizes why Boo is acting out and she knows just how to help him. Boo the Library Ghost is an adorable picture book that follows one rambunctious ghost who really just wants to learn how to read. Poppy is there to teach Boo how to read and soon enough he becomes the friendliest library ghost around!"--
Keywords: Ghosts -- Juvenile fiction; Girls -- Juvenile fiction; Libraries -- Juvenile fiction; Books and reading -- Juvenile fiction; Ghosts -- Fiction; Girls -- Fiction; Libraries -- Fiction; Books and reading -- Fiction; Ghost stories; Picture books